A case of long-term hypothyroidism converted to hyperthyroidism secondary to an autoimmune trigger - R., Shreenidhi; Sivasamy, Manoj; S., Prasanna Karthik; Bathena, Arun Kumar; ., Nishaanth (International Journal of Advances in Medicine, 2022)
Primary hypothyroidism is a common endocrine condition that is encountered. Graves disease and Hashimoto’s thyroiditis are the most common autoimmune conditions in which conversion of hyperthyroidism to hypothyroidism is seen. Chances of conversion of hypothyroidism to hyperthyroidism is extremely rare. This case highlights that there should be a high index of suspicion for a possible conversion of hypothyroidism to hyperthyroidism. The etiology being an autoimmune switch by an external stimulus in genetically susceptible individuals. Hereby, presenting a case of 53-years female, who is a known case of type II diabetes mellitus, chronic kidney disease, nephrotic syndrome diagnosed with minimal change disease who presented with a hormonal profile showing hyperthyroidism. She had a history of hypothyroidism in the past for 12-years and was treated with levothyroxine and was off treatment for the past 2 years. Further evaluation showed presence of primary Sjogren’s syndrome which has let to this conversion.